Modified TB polymer, preparation method and application of modified TB polymer in aluminum alloy surface coating

By introducing modified TB polymer into the aluminum alloy surface composite coating, the problems of uneven internal stress and uneven dispersion of nanomaterials during the curing process are solved, and the coating is high adhesion, flexibility and corrosion protection are achieved. Improved performance while ensuring the stability and environmental protection of the coating.

CN119505234AActive Publication Date: 2025-02-25SHANDONG UNIV

Patent Information

Application Number
CN202510072484.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-02-25
Estimated Expiration
2045-01-17

AI Technical Summary

Technical Problem

During the curing process, the existing aluminum alloy surface coating is prone to internal stress due to uneven volume shrinkage, resulting in cracks in the coating, affecting the stability of its anti-corrosion effect. At the same time, the dispersion of nanomaterials in the coating is uneven, affecting the overall performance.

Method used

By introducing modified TB polymer into the aluminum alloy surface composite coating, the modified TB polymer reacts with metal substrates such as grafted alkane groups and OH groups to improve the epoxy resin coating and metal substrates. Adhesion and uniformly disperse the nanomaterials through reaction with inorganic fillers, optimizing the density and corrosion resistance of the coating.

Benefits of technology

The modified TB polymer enhances the flexibility and metal adhesion of the coating, avoids the problem of internal stress unevenness in the coating during curing, improves the corrosion resistance and stability of the coating, and at the same time achieves uniform dispersion of nano-inorganic fillers, enhancing the density and environmental protection of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505234A_ABST
    Figure CN119505234A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of materials, and particularly relates to a modified TB polymer, a preparation method and application of the modified TB polymer in an aluminum alloy surface coating. The prepared modified TB polymer has a structure as shown in a formula I, is used as a flexibilizer component in an aluminum alloy surface coating, can provide a large number of hydrophilic hydroxyl or carboxyl groups which are easily subjected to an activation reaction with a metal surface, and improves the adhesive force of the coating; meanwhile, the group can also improve the dispersity of the filler, so that the coating is more uniform, the stress effect of the coating can be improved, and the coating has better flexibility. In addition, a modified TB polymer is introduced into the coating, so that the prepared coating is green and environment-friendly, excellent in salt fog resistance and chemical corrosion resistance, capable of adapting to a complex marine environment, capable of well protecting metal materials and capable of prolonging the service life of the metal materials. And # imgabs0 # I is adopted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of materials, and in particular relates to a modified TB polymer, a preparation method and application thereof in aluminum alloy surface coating. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Aluminum alloys are widely used in aerospace, shipbuilding, automobiles and other fields due to their advantages of light weight, high specific strength, excellent mechanical properties, and easy processing and forming. However, since most metal materials such as aluminum alloys are exposed to the natural environment for a long time, corrosion is inevitable. This corrosion will not only lead to a decrease in material strength or failure, but also shorten the service life of the equipment and may even cause major safety accidents and property losses.

[0004] In order to improve its anti-corrosion performance, coating a layer of protective anti-corrosion coating on the surface of aluminum alloy is an effective method and measure to prevent corrosion of the substrate through shielding, corrosion inhibition, cathodic protection and other effects. Traditional anti-corrosion coatings usually add chromate fillers to the coating to achieve passivation and slow-release effects. These fillers rely on the sealing effect of chromate ions to protect the surface of aluminum alloy. However, due to the serious harm of hexavalent chromium to the environment and human health, its use has been strictly restricted. In recent years, the research and application of environmentally friendly coating technology without chromate fillers has gradually become the focus of the development of the anti-corrosion industry.

[0005] Anticorrosion coatings with epoxy resin as the main component have become the focus of attention for anticorrosion coatings due to their excellent weather resistance and anticorrosion properties. However, epoxy resin has weak bonding with the surface of aluminum alloy, and is prone to generate internal stress due to uneven volume shrinkage during the curing process, which often leads to cracks in the coating, thereby affecting the stability of its anticorrosion effect. The introduction of inorganic nanomaterials into epoxy resin can significantly enhance the coating's barrier ability to water molecules, oxygen and corrosive ions, thereby greatly improving its anticorrosion performance. However, due to the high surface energy of nanomaterials, they are prone to agglomeration, resulting in uneven dispersion in the coating, which affects the overall performance of the coating. To solve the above problems, the key is to optimize the stress characteristics of epoxy resin, improve the uniform dispersion of nanofillers in it, and enhance its compatibility with the coating solution.

[0006] Tröger's Base (TB) polymers are a class of polymers with microporous structures. Due to the unique twisted structure of the molecules themselves and excellent mechanical, thermal and chemical properties, they have attracted extensive attention and research in the fields of gas separation membranes, anion exchange membranes and ultrafiltration membranes in recent years. TB polymers are prepared by the step-by-step polymerization of aromatic diamine monomers with dimethoxymethane in trifluoroacetic acid solution. Due to the presence of a large number of fused rings in the TB structure, the structure is highly rigid. The chemical structure and physical properties of TB polymers can usually be adjusted by adjusting and designing repeating units or a large number of side chain structures. Summary of the invention

[0007] In view of the problems existing in the prior art, the present invention provides a modified TB polymer, a preparation method and an application thereof in an aluminum alloy surface coating. By introducing the modified TB polymer into the composite coating on the aluminum alloy surface, the obtained coating is not only environmentally friendly, but also has the characteristics of good flexibility and strong metal adhesion, and can meet the durability requirements of the anti-corrosion coating.

[0008] In order to achieve the above object, the present invention adopts the following technical solution: The first aspect of the present invention provides a modified TB polymer, wherein the modified TB polymer has a structure as shown in Formula I: Formula I; Among them, R is selected from , , , and One or more of the .

[0009] The second aspect of the present invention provides a method for preparing the above-mentioned modified TB polymer, specifically: The TB polymer and the halogenated compound RX are mixed and dissolved in an organic solvent, heated for reaction, cooled to room temperature, washed, and vacuum dried to obtain a modified TB polymer; wherein R in the halogenated compound RX is selected from , , , , One of: X is selected from one or more of fluorine, chlorine, bromine and iodine.

[0010] Preferably, the synthesis reaction formula is as follows:

[0011] Preferably, the halogenated compound RX is selected from one or more of 3-bromo-1,2-diphenol, 4-bromobutyric acid, 5-bromo-2-methylpyridine, 3-bromopropylamine, and 4-bromopiperidine.

[0012] Preferably, the mass ratio of the halogenated compound RX to the TB polymer is 2-8:1.

[0013] Preferably, the heating reaction is carried out at a temperature of 20 to 80° C. and for a time of 6 to 48 h.

[0014] Preferably, the organic solvent is one of dichlorobenzene, chloroform, ether and N-methylpyrrolidone.

[0015] Preferably, the mass ratio of the organic solvent to the TB polymer is 3-20:1.

[0016] Preferably, the specific synthesis process of the TB polymer is: under an inert atmosphere, 4,4'-diamino-3,3'-dimethylbiphenyl is used as a raw material and trifluoroacetic acid is used as a catalyst, and reacts with paraformaldehyde in an organic solvent to obtain the TB polymer. The synthesis reaction formula is as follows: .

[0017] Further preferably, the mass ratio of trifluoroacetic acid to 4,4'-diamino-3,3'-dimethylbiphenyl is 1:10~50; the mass ratio of the organic solvent to 4,4'-diamino-3,3'-dimethylbiphenyl is 3~5:1; the mass ratio of paraformaldehyde to 4,4'-diamino-3,3'-dimethylbiphenyl is 1.2~3:1; the pressure is normal pressure; and the inert atmosphere is selected from one or more of argon and nitrogen.

[0018] Further preferably, the organic solvent is selected from one or more of dimethylacetamide, methanol, chloroform, diethyl ether, and N-methylpyrrolidone.

[0019] More preferably, the reaction temperature is 0-5°C and the reaction time is 3-72 h.

[0020] The third aspect of the present invention provides a wear-resistant and corrosion-resistant composite coating, comprising the modified TB polymer described in the first aspect.

[0021] Preferably, the modified TB polymer is used as a toughening agent component in the wear-resistant and corrosion-resistant composite coating.

[0022] Preferably, the wear-resistant and corrosion-resistant composite coating further includes epoxy resin, inorganic filler, graphene, anti-settling agent, curing agent, leveling agent, organic solvent M and organic solvent N.

[0023] Preferably, the wear-resistant and anti-corrosion composite coating comprises, by weight, 15 to 45 parts of epoxy resin, 1 to 20 parts of modified TB polymer, 5 to 20 parts of inorganic filler, 15 to 40 parts of organic solvent M, 0.5 to 5 parts of graphene, 0.5 to 5 parts of anti-settling agent, 35 to 80 parts of curing agent, 2 to 10 parts of leveling agent, and 15 to 55 parts of organic solvent N.

[0024] Further preferably, the epoxy resin is selected from one or more of epoxy resin E44, epoxy resin E42, and epoxy resin E20; the inorganic filler is selected from one or more of barium sulfate powder, aluminum tripolyphosphate, kaolin powder, and mica powder; the organic solvent M is selected from one or more of xylene, butyl acetate, ethyl acetate, n-butanol, and isopropanol; the anti-settling agent is bentonite; the curing agent is selected from one or more of aliphatic polyamine curing agents, aliphatic amine adduct curing agents, and polyamide curing agents, preferably polyamide 650; the leveling agent is selected from one or more of polydimethylsiloxane and polyacrylate leveling agents; the organic solvent N is selected from one or more of ethylbenzene, ethyl acetate, n-butanol, and propylene glycol methyl ether acetate.

[0025] Further preferably, the particle size of the inorganic filler and graphene is 200-600 mesh, more preferably 300-400 mesh.

[0026] A fourth aspect of the present invention provides a method for preparing the wear-resistant and corrosion-resistant composite coating according to the third aspect, comprising the following steps: S1, adding modified TB polymer, inorganic filler, graphene, and anti-settling agent to a mixture of epoxy resin and organic solvent M in sequence, stirring and reacting, to obtain component A; S2, mixing the curing agent, the leveling agent and the organic solvent N and stirring to react to obtain component B; S3. Mix component A and component B to obtain a wear-resistant and anti-corrosion composite coating.

[0027] Preferably, in step S1, the stirring reaction is carried out at a temperature of 15-30°C, for a time of 0.5-3 h, and at a speed of 200-2000 r / min.

[0028] Preferably, in step S2, the stirring reaction is carried out at a temperature of 15-30°C, for a time of 0.5-3 h, and at a speed of 200-2000 r / min.

[0029] Preferably, in step S3, the weight ratio of component A to component B is 100:30-80.

[0030] The fifth aspect of the present invention provides an application of the wear-resistant and anti-corrosion composite coating described in the third aspect and / or the wear-resistant and anti-corrosion composite coating prepared by the preparation method described in the fourth aspect in the field of anti-corrosion coatings.

[0031] The beneficial effects achieved by one or more technical solutions of the present invention are as follows: (1) The present invention adds a novel modified TB polymer toughening agent to the anti-corrosion coating. After the TB polymer is modified, a large number of alkane groups are grafted. The OH groups will undergo an activation reaction with metal substrates such as aluminum alloys, and then hydrogen desorption will occur, resulting in a dispersed interface portion, which significantly improves the adhesion between the epoxy resin coating and metal substrates such as aluminum alloys.

[0032] (2) The large number of OH groups on the TB polymer prepared by the present invention can react with the surface of inorganic fillers such as graphene in the coating, so that the inorganic fillers can be evenly distributed in the resin, avoiding the agglomeration problem of nano-inorganic fillers, strengthening the density of the composite coating, and effectively resisting the penetration of water molecules, oxygen and electrolytes, thereby improving the anti-corrosion performance of the coating; at the same time, the nano-inorganic fillers replace conventional toxic fillers such as chromate, making the coating green and environmentally friendly.

[0033] (3) The modified TB polymer toughening agent added in the present invention can effectively improve the problems of cracks and micropores caused by uneven internal stress in the coating during the curing process, increase the flexibility of the coating, and effectively prevent the corrosion caused by the micropores and microcracks of the coating entering through diffusion movement of corrosive substances, thereby improving the anti-corrosion performance of the coating and extending the service life of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0035] Figure 1 This is a Fourier transform infrared spectrum of the modified TB polymer prepared in Example 1 of the present invention; Figure 2 A scanning electron microscope image (SEM) of the modified TB polymer prepared in Example 1 of the present invention; Figure 3 This is a Fourier transform infrared spectrum of the modified TB polymer prepared in Example 4 of the present invention; Figure 4 This is a scanning electron microscope image of the modified TB polymer prepared in Example 4 of the present invention; Figure 5 This is the Fourier transform infrared spectrum of the TB polymer prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0036] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0037] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.

[0038] Example 1: This example provides a modified TB polymer and a method for preparing the same (1) Preparation of TB polymer: Under an inert atmosphere, 15 g of 4,4'-diamino-3,3'-dimethylbiphenyl and 60 g of dimethylacetamide were mixed and stirred at 5°C under normal pressure until the mixture was uniformly mixed. 45 g of paraformaldehyde was added and stirred. 1 g of trifluoroacetic acid was added dropwise to the mixture solution and the reaction was continued for 12 h to obtain a TB polymer.

[0039] (2) Preparation of modified TB polymer: Add 10 g of TB polymer prepared in step (1) into 50 g of chloroform, add 30 g of 3-bromo-1,2-diphenol, and react at 20° C. for 10 h to obtain a modified TB polymer toughening agent.

[0040] Figure 1 The Fourier transform infrared spectrum of the modified TB polymer in the wear-resistant and anti-corrosion composite coating for the aluminum alloy surface in this embodiment is shown in FIG. 1 ; it can be confirmed that the structural formula of the Tröger's Base polymer prepared in the present invention is:

[0041] Depend on Figure 1 It can be seen that the Fourier transform infrared spectrum shows that the infrared spectrum of the modified TB polymer is basically similar to that of the TB polymer ( Figure 5 ), but at 3020 cm -1 The characteristic absorption peak of -OH group appeared at 1425 cm -1 Where CN indicates quaternary ammonium salt + The characteristic absorption peak of 3-bromo-1,2-diphenol was successfully grafted into the TB polymer.

[0042] Depend on Figure 2 It can be seen that the scanning electron microscope image shows that the modified TB polymer prepared in this example is in the form of slender fibers. After adding it into the coating, the tear resistance and stress-strain capacity of the coating can be further enhanced, and the corrosion resistance of the coating can be improved.

[0043] Example 2: This example provides a modified TB polymer and a method for preparing the same (1) Preparation of TB polymer: Under an inert atmosphere, 30 g of 4,4'-diamino-3,3'-dimethylbiphenyl and 90 g of chloroform were mixed and stirred at 5°C under normal pressure until the mixture was uniformly mixed. Then 36 g of paraformaldehyde was added and stirred. 3 g of trifluoroacetic acid was added dropwise to the mixture solution and the reaction was continued for 12 h to obtain a TB polymer.

[0044] (2) Preparation of modified TB polymer: Add 10 g of TB polymer prepared in step (1) into 30 g of chloroform, add 20 g of 5-bromo-2-methylpyridine, and react at 60° C. for 24 h to obtain a modified TB polymer toughening agent.

[0045] Data characterization: at 1600~1650 cm -1 and 1450-1500 cm -1 The peaks in the range may represent characteristic absorption peaks caused by the vibration of the six-membered ring skeleton in the piperidine molecule, which indicates that the piperidine-containing group is grafted onto the TB polymer. It can be confirmed that the structural formula of the Tröger's Base polymer prepared in this example is:

[0046] Example 3: This example provides a modified TB polymer and a method for preparing the same (1) Preparation of TB polymer: Under an inert atmosphere, 30 g of 4,4'-diamino-3,3'-dimethylbiphenyl and 100 g of N-methylpyrrolidone were mixed and stirred at 0°C and normal pressure until the mixture was uniformly mixed. Then, 60 g of polyformaldehyde was added and stirred. 1 g of trifluoroacetic acid was added dropwise to the mixture solution and the reaction was continued for 6 h to obtain a TB polymer.

[0047] (2) Preparation of modified TB polymer: Add 10 g of TB polymer prepared in step (1) to 30 g of N-methylpyrrolidone, add 50 g of 3-bromopropylamine, and react at 30° C. for 48 h to obtain a modified TB polymer toughening agent.

[0048] Data characterization: 3400~3200 cm -1 The double peaks at the positions may represent the characteristic absorption peak of -NH2, which indicates that the alkane with an amine group is grafted onto the TB polymer. It can be confirmed that the structural formula of the Tröger's Base polymer prepared in this example is:

[0049] Example 4: This example provides a modified TB polymer and a method for preparing the same (1) Preparation of TB polymer: Under an inert atmosphere, 50 g of 4,4'-diamino-3,3'-dimethylbiphenyl and 150 g of chloroform were mixed and stirred at 0°C and normal pressure until the mixture was uniformly mixed. Then, 75 g of paraformaldehyde was added and stirred. 1 g of trifluoroacetic acid was added dropwise to the mixture solution and the reaction was continued for 72 h to obtain a TB polymer.

[0050] (2) Preparation of modified TB polymer: Add 10 g of TB polymer prepared in step (1) into 40 g of chloroform, add 80 g of 4-bromobutyric acid, and react at 30° C. for 24 h to obtain a modified TB polymer toughening agent.

[0051] Figure 3 The Fourier transform infrared spectrum of the modified TB polymer in the wear-resistant and anti-corrosion composite coating for the aluminum alloy surface in this embodiment is shown in FIG. 1 . It can be confirmed that the structural formula of the Tröger's Base polymer obtained in this embodiment is:

[0052] Depend on Figure 3 It can be seen that the Fourier transform infrared spectrum shows that at 1746 cm -1 The characteristic absorption peak representing C=O appears at 3020 cm -1 The appearance of the characteristic absorption peak of the -OH group at the TB polymer indicates that the carboxyl group has been successfully grafted onto the TB polymer, achieving the modification of the TB polymer.

[0053] Depend on Figure 4 It can be seen that the scanning electron microscope image shows that the modified TB polymer is in the form of slender fibers. After adding it into the coating, the tear resistance and stress-strain capacity of the coating can be further enhanced, and the corrosion resistance of the coating can be improved.

[0054] Example 5: This example provides a modified TB polymer and a method for preparing the same (1) Preparation of TB polymer: Under an inert atmosphere, 10 g of 4,4'-diamino-3,3'-dimethylbiphenyl and 50 g of chloroform were mixed and stirred at 0°C and normal pressure until the mixture was uniformly mixed. Then 20 g of paraformaldehyde was added and stirred. 1 g of trifluoroacetic acid was added dropwise to the mixture solution and the reaction was continued for 24 h to obtain a TB polymer.

[0055] (2) Preparation of modified TB polymer: Add 10 g of TB polymer prepared in step (1) to 30 g of dichlorobenzene, add 30 g of 4-bromopiperidine, and react at 30° C. for 8 h to obtain a modified TB polymer toughening agent.

[0056] Data characterization: at 1600~1650 cm -1and 1450-1500 cm -1 The peaks in the range may represent characteristic absorption peaks caused by the vibration of the six-membered ring skeleton in the piperidine molecule, which indicates that the piperidine-containing group is grafted onto the TB polymer. It can be confirmed that the structural formula of the Tröger's Base polymer prepared in this example is:

[0057] Comparative Example 1: The difference between this comparative example and Example 1 is that only the preparation in step (1) is performed, and the modification operation in step (2) is not performed.

[0058] Data representation: Figure 5 As shown, at 1461 cm -1 The C=C characteristic absorption peak representing the benzene ring appeared at 1664cm -1 The characteristic absorption peak representing the CN bond appeared at 1089 cm -1 and 800 cm -1 The characteristic absorption peaks representing CNC bonds appeared at 2928 cm -1 A characteristic absorption peak representing -CH3 appeared at , and the appearance of the above characteristic peak indicated that the TB polymer had been successfully synthesized.

[0059] Application Example 1: This application example provides a wear-resistant and anti-corrosion composite coating for aluminum alloy surface and a preparation method thereof. The specific steps are as follows: The wear-resistant and anti-corrosion composite coating prepared in this embodiment includes, by weight: 30 parts of epoxy resin, 10 parts of modified TB polymer toughening agent prepared in Example 1, 10 parts of ethyl acetate, 20 parts of aluminum tripolyphosphate, 2 parts of graphene, 1.5 parts of diatomaceous earth, 35 parts of polyamide 650, 30 parts of n-butanol, and 5 parts of polydimethylsiloxane.

[0060] The preparation method is specifically as follows: (1) Add 10 parts by weight of modified TB polymer toughening agent and 40 parts by weight of ethyl acetate to 30 parts by weight of epoxy resin, stir for 1 h at a reaction temperature of 20°C and a stirring speed of 200 r / min. Then add 20 parts by weight of aluminum tripolyphosphate, 2 parts by weight of graphene and 1.5 parts by weight of diatomaceous earth, stir for 2 h at a reaction temperature of 20°C and a stirring speed of 800 r / min to obtain component A; (2) Add 30 parts by weight of n-butanol to 35 parts by weight of polyamide 650, stir evenly, then add 5 parts by weight of polydimethylsiloxane, stir at a reaction temperature of 20°C for 1 h at a stirring speed of 300 r / min to obtain component B; (3) 100 parts by weight of component A and 70 parts by weight of component B are mixed and coated on the surface of the aluminum alloy metal after sandblasting. After curing for 24 hours, a wear-resistant and anti-corrosion composite coating for the aluminum alloy surface is obtained.

[0061] Application Example 2: This application example provides a wear-resistant and anti-corrosion composite coating for aluminum alloy surface and a preparation method thereof. The specific steps are as follows: The wear-resistant and anti-corrosion composite coating prepared in this embodiment includes, by weight: 40 parts of epoxy resin, 10 parts of the modified TB polymer toughening agent prepared in Example 2, 40 parts of ethyl acetate, 15 parts of aluminum tripolyphosphate, 2 parts of graphene, 1 part of diatomaceous earth, 40 parts of polyamide 650, 30 parts of n-butanol, and 5 parts of polydimethylsiloxane.

[0062] The preparation method is as follows: (1) adding 10 parts by weight of a modified TB polymer toughening agent and 40 parts by weight of ethyl acetate to 40 parts by weight of epoxy resin, stirring for 1 h at a reaction temperature of 20°C and a stirring speed of 200 r / min. Then adding 15 parts by weight of aluminum tripolyphosphate, 2 parts by weight of graphene and 1 part by weight of diatomaceous earth, stirring for 2 h at a reaction temperature of 20°C and a stirring speed of 800 r / min to obtain component A; (2) Add 30 parts by weight of n-butanol to 40 parts by weight of polyamide 650, stir evenly, then add 5 parts by weight of polydimethylsiloxane, stir at a reaction temperature of 20°C for 1 h at a stirring speed of 300 r / min to obtain component B; (3) 100 parts by weight of component A and 70 parts by weight of component B are mixed and coated on the surface of the aluminum alloy metal after sandblasting. After curing for 24 hours, a wear-resistant and anti-corrosion composite coating for the aluminum alloy surface is obtained.

[0063] Application Example 3: This application example provides a wear-resistant and anti-corrosion composite coating for aluminum alloy surface and its preparation method. The specific steps refer to Application Example 1. The difference from Application Example 1 is that in step (1), the modified TB polymer toughening agent prepared in Example 3 is added to this embodiment, and the contents of other components and the preparation method are consistent with those in Application Example 1.

[0064] Application Example 4: This application example provides a wear-resistant and anti-corrosion composite coating for aluminum alloy surfaces and a preparation method thereof. The specific steps refer to Application Example 1. The difference from Application Example 1 is that in step (1), the modified TB polymer toughening agent prepared in Example 4 is added to this embodiment, and the contents of other components and the preparation method are consistent with those in Application Example 1.

[0065] Application Example 5: This application example provides a wear-resistant and anti-corrosion composite coating for aluminum alloy surfaces and a preparation method thereof. The specific steps refer to Application Example 2. The difference from Application Example 2 is that in step (1), the modified TB polymer toughening agent prepared in Example 5 is added to this embodiment, and the contents of other components and the preparation method are consistent with those in Application Example 1.

[0066] Application Example 6: This application example provides a wear-resistant and anti-corrosion composite coating for aluminum alloy surfaces and a preparation method thereof. The specific steps refer to Application Example 1. The difference from Application Example 1 is that in step (1) of this embodiment, the TB polymer toughening agent prepared in Comparative Example 1 is added, and the contents of other components and the preparation method are consistent with those in Application Example 1.

[0067] Application Example 7: This application example provides a wear-resistant and anti-corrosion composite coating for aluminum alloy surface and its preparation method. The specific steps refer to Application Example 1. The difference from Application Example 1 is that in step (1) of this application example, no modified TB polymer toughening agent is added, and the contents of other components and the preparation method are consistent with those of Application Example 1.

[0068] Test Example 1: This test example is to test the wear-resistant and anti-corrosion composite coatings prepared in Application Examples 1 to 7 in a salt spray test chamber for salt spray resistance and mechanical properties. Among them, the corrosion resistance test is carried out in accordance with GB / T 1771-2007 "Determination of neutral salt spray resistance of paints and varnishes"; the adhesion test is carried out in accordance with GB / T 5210-2006 "Paints and varnishes pull-off adhesion test"; the pencil hardness of the paint film is carried out in accordance with GB / T 6739-2006 "Paint and coating pencil method for determination of paint film hardness"; the wear resistance is tested in accordance with GB / T 1768-2006 "Determination of wear resistance of paint films"; the impact resistance is tested in accordance with GB / T 1732-93 "Determination of impact resistance of paint films".

[0069] The test results are shown in Table 1 and Table 2: Table 1 Salt spray resistance test of wear-resistant and corrosion-resistant composite coating

[0070] Table 2 Mechanical properties test of wear-resistant and corrosion-resistant composite coating

[0071] It can be seen from the test results of Table 1 and Table 2 that, compared with Application Example 6, the modified TB polymer toughening agent is added in Application Example 1 of the present invention, and the salt spray resistance and mechanical properties of the obtained coating are improved; compared with Application Example 7 without the modified TB polymer toughening agent, the modified toughening agent added in Application Example 1 of the present invention can utilize its hydrophilic group to better react with the hydroxyl groups on the surface of the inorganic filler and the metal base, significantly improving the adhesion of the coating, and the salt spray resistance and mechanical properties of the obtained coating are better.

[0072] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A modified TB polymer, characterized in that The modified TB polymer has a structure shown in Formula I: Formula I; Among them, R is selected from , , , and One or more of the .

2. A method for preparing the modified TB polymer according to claim 1, characterized in that: Specifically, the TB polymer and the halogenated compound RX are mixed and dissolved in an organic solvent, heated for reaction, cooled to room temperature, washed, and vacuum dried to obtain the modified TB polymer; wherein R in the halogenated compound RX is selected from , , , , One of: X is selected from one or more of fluorine, chlorine, bromine and iodine.

3. The method for preparing the modified TB polymer according to claim 2, characterized in that: The halogenated compound RX is selected from one or more of 3-bromo-1,2-diphenol, 4-bromobutyric acid, 5-bromo-2-methylpyridine, 3-bromopropylamine, and 4-bromopiperidine; the mass ratio of the halogenated compound RX to the TB polymer is 2-8:1; the organic solvent is one of dichlorobenzene, chloroform, ether, and N-methylpyrrolidone; the temperature of the heating reaction is 20-80°C, and the time is 6-48 h; the mass ratio of the organic solvent to the TB polymer is 3-20:

1.

4. The method for preparing the modified TB polymer according to claim 2, characterized in that: The specific synthesis process of the TB polymer is: under an inert atmosphere, using 4,4'-diamino-3,3'-dimethylbiphenyl as a raw material and trifluoroacetic acid as a catalyst, reacting with paraformaldehyde in an organic solvent to obtain the TB polymer; Wherein, the mass ratio of trifluoroacetic acid to 4,4'-diamino-3,3'-dimethylbiphenyl is 1:10~50; the mass ratio of the organic solvent to 4,4'-diamino-3,3'-dimethylbiphenyl is 3~5:1; the mass ratio of paraformaldehyde to 4,4'-diamino-3,3'-dimethylbiphenyl is 1.2~3:1; the pressure is normal pressure; the inert atmosphere is selected from one or more of argon and nitrogen.

5. The method for preparing the modified TB polymer according to claim 2, characterized in that, The organic solvent is selected from one or more of dimethylacetamide, methanol, chloroform, ether, and N-methylpyrrolidone; the reaction temperature is 0-5°C, and the reaction time is 3-72 h.

6. A wear-resistant and anti-corrosion composite coating, characterized in that: The wear-resistant and anti-corrosion composite coating comprises, by weight, 15 to 45 parts of epoxy resin, 1 to 20 parts of modified TB polymer, 5 to 20 parts of inorganic filler, 15 to 40 parts of organic solvent M, 0.5 to 5 parts of graphene, 0.5 to 5 parts of anti-settling agent, 35 to 80 parts of curing agent, 2 to 10 parts of leveling agent and 15 to 55 parts of organic solvent N.

7. The wear-resistant and anti-corrosion composite coating according to claim 6, characterized in that: The epoxy resin is selected from one or more of epoxy resin E44, epoxy resin E42, and epoxy resin E20; the inorganic filler is selected from one or more of barium sulfate powder, aluminum tripolyphosphate, kaolin powder, and mica powder; the organic solvent M is selected from one or more of xylene, butyl acetate, ethyl acetate, n-butanol, and isopropanol; the anti-settling agent is bentonite; the curing agent is selected from one or more of aliphatic polyamine curing agents, aliphatic amine adduct curing agents, and polyamide curing agents; the leveling agent is selected from one or more of polydimethylsiloxane and polyacrylate leveling agents; the organic solvent N is selected from one or more of ethylbenzene, ethyl acetate, n-butanol, and propylene glycol methyl ether acetate.

8. A method for preparing the wear-resistant and corrosion-resistant composite coating according to any one of claims 6 to 7, characterized in that: The following steps are involved: S1, adding modified TB polymer, inorganic filler, graphene, and anti-settling agent to a mixture of epoxy resin and organic solvent M in sequence, stirring and reacting, to obtain component A; S2, mixing the curing agent, the leveling agent and the organic solvent N and stirring to react to obtain component B; S3. Mix component A and component B to obtain a wear-resistant and anti-corrosion composite coating.

9. The method for preparing the wear-resistant and corrosion-resistant composite coating according to claim 8, characterized in that: In step S1, the stirring reaction temperature is 15-30°C, the time is 0.5-3 h, and the speed is 200-2000 r / min; In step S2, the stirring reaction temperature is 15-30°C, the time is 0.5-3 h, and the speed is 200-2000 r / min; In step S3, the weight ratio of component A to component B is 100:30-80.

10. Use of the modified TB polymer according to claim 1 and / or the wear-resistant and anti-corrosion composite coating according to any one of claims 6 to 7 in the field of anti-corrosion coatings.

Citation Information

Patent Citations

  • TROGER's base polymers having intrinsic microporosity

    CN108291026A

  • Composite material modified wear-resistant and corrosion-resistant coating as well as preparation method thereof

    CN110527404A

  • Heavy-duty anti-corrosion coating for aluminum alloy surfaces and preparation method thereof

    CN111019478A

  • TB polymer ion exchange membrane material containing anion / cation / zwitterionic structure as well as preparation method and application of TB polymer ion exchange membrane material

    CN113563581A

  • Ionized Troger base high polymer material as well as preparation method and application thereof

    CN115636936A

Cited By

  • Method for detecting surface defects of aluminum alloy plate with epoxy coating

    CN121208294A

  • Intermediate, modified hydrophobic TB polymer as well as preparation method and application of modified hydrophobic TB polymer

    CN121554736A

  • Intermediates, modified hydrophobic tb polymers, and methods of making and using the same

    CN121554736B